The assessment surgical treatment of distant results of the peritrochanteric femur fractures by using Dynamic Hip Stabilizers - Sienkiewicz, Dariusz (2008)
The presented study considers problems associated with peritrochanteric femur fractures (PFF) using dynamic hip stabilizers (DSB). The aim of the study was evaluation of distant operative treatment outcomes of these fractures using DHS and answering of the following questions: What are the long-term functional and radiological outcomes of surgical treatment of the PFF using DSB according to sex in age groups and type of fracture according to Boyd-Gryffin’s scale ? What does the success of DSB use in surgical treatment of the PFF depend on ? What are the most frequent complications and failures ? The study was conducted on 142 patients. To estimate the type of fracture, Boyd-Griffin’s scale was used. To estimate functional effects, the Harris scale was used. To estimate radiological outcomes, criteria from Golec et al. were used. Analysis results can lead us to the following conclusions: Surgical treatment of the PFF using DSB in patients aged up to 65 with type I and II fractures Boyd-Griffin’s scale, can lead to very good and good functional and radiological results, irrespective of gender. Surgical treatment of the PFF using DSB in patients over 65 with type III and IV fractures Boyd-Griffin’s scale, can lead to satisfactory or poor results, especially in women. The effectiveness of PFF surgery using DHS depends on age, the type of fracture and accurate surgery technique.
Keywords: DSB; peritrochanteric fractures; surgical treatment